Impacts of Cucurbit Chlorotic Yellows Virus (CCYV) on Biological Characteristics of Its Vector Bemisia tabaci (Hemiptera: Aleyrodidae) MED Species. Issue 5 (29th October 2021) - He, Haifang; Li, Jingjing; Zhang, Zelong; Tang, Xuefei; Song, Danyang; Yan, Fengming
Abstract: Plant viruses can change the phenotypes and defense pathways of the host plants and the performance of their vectors to facilitate their transmission. Cucurbit chlorotic yellows virus (CCYV) ( Crinivirus ), a newly reported virus occurring on cucurbit plants and many other plant species, is transmitted specifically by Bemisia tabaci MEAM1 (B biotype) and MED (Q biotype) cryptic species in a semipersistent manner. This study evaluated the impacts of CCYV on B. tabaci to better understand the plant-virus-vector interactions. By using CCYV- B. tabaci MED - cucumber as the model, we investigated whether or how a semipersistent plant virus impacts the biology of its whitefly vector. CCYV mRNAs were detectable in nymphs from first to fourth instars and adults of B. tabaci with different titers. Nymph instar durations and adult longevity of female whiteflies greatly extended on CCYV-infected plants, but nymph instar durations and adult longevity of male whiteflies were not significantly influenced. In addition, the body length and oviposition increased in adults feeding on CCYV-infected plants, but the hatching rates of eggs and survival rates of different stages were not affected. Most interestingly, the sex ratio (male:female) significantly reduced to 0.5:1 in whitefly populations on CCYV-infected plants, while the ratio remained about 1:1 on healthy plants. These results indicated that CCYV can significantly impact the biological characteristics of its vector B. tabaci . It is speculated that CCYV and B. tabaci have established a typical mutualist relationship mediated by host plants.